Ten-Year Study of the Stringently Defined Otitis-prone Child in Rochester, NY. Issue 9 (September 2016) - Pichichero, Michael E.
Abstract : This review summarizes a prospective, longitudinal 10-year study in Rochester, NY, with virtually every clinically diagnosed acute otitis media (AOM) confirmed by bacterial culture of middle ear fluid. Children experiencing 3 episodes within 6 months or 4 episodes in 12 months were considered stringently defined otitis prone (sOP). We found stringent diagnosis compared with clinical diagnosis reduced the frequency of children meeting the OP definition from 27% to 6% resulting in 14.8% and 2.4% receiving tympanostomy tubes, respectively. Significantly more often respiratory syncytial virus infection led to AOM in sOP than non-otitis-prone children that correlated with diminished total respiratory syncytial virus-specific serum IgG. sOP children produced low levels of antibody to Streptococcus pneumoniae and Haemophilus influenzae candidate vaccine protein antigens and to routine pediatric vaccines. sOP children generated significantly fewer memory B cells, functional and memory T cells to otopathogens following nasopharyngeal colonization and AOM than non-otitis-prone children and they had defects in antigen-presenting cells. Abstract : Supplemental Digital Content is available in the text.